2011
DOI: 10.1182/blood-2010-09-309989
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Flt3+CD150− myeloid progenitors in adult mouse bone marrow that harbor T lymphoid developmental potential

Abstract: Common myeloid progenitors (CMPs) were first identified as progenitors that were restricted to myeloid and erythroid lineages. However, it was recently demonstrated that expression of both lymphoidand myeloid-related genes could be detected in myeloid progenitors. Furthermore, these progenitors were able to give rise to T and B lymphocytes, in addition to myeloid cells. Yet, it was not known whether these progenitors were multipotent at the clonogenic level or there existed heterogeneity within these progenito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…For example, different phenotypes with persisting GM differentiation potentialities in combination with other different lineage options have now been reported ( Figure 2C-D). [103][104][105][106][107] Additional deviations from a unilinear branching model of hematopoietic cell differentiation from a single original compartment include examples of a very rapid loss of LTRC properties with full retention of viability and proliferative responsiveness in vitro 65 or a rapid differentiation of their progeny into mature cells in vivo. 93,108 Also of note is the suggestion that the unexpectedly accelerated differentiation profiles exhibited by some cells with an LTRC phenotype may be related to their particular "poised" or "primed" gene expression state-as reflected in their expression of certain lineage-specific genes at a low level.…”
Section: Ltrc Differentiation Controlmentioning
confidence: 99%
“…For example, different phenotypes with persisting GM differentiation potentialities in combination with other different lineage options have now been reported ( Figure 2C-D). [103][104][105][106][107] Additional deviations from a unilinear branching model of hematopoietic cell differentiation from a single original compartment include examples of a very rapid loss of LTRC properties with full retention of viability and proliferative responsiveness in vitro 65 or a rapid differentiation of their progeny into mature cells in vivo. 93,108 Also of note is the suggestion that the unexpectedly accelerated differentiation profiles exhibited by some cells with an LTRC phenotype may be related to their particular "poised" or "primed" gene expression state-as reflected in their expression of certain lineage-specific genes at a low level.…”
Section: Ltrc Differentiation Controlmentioning
confidence: 99%
“…NHCs have been suggested to be of lymphocytic origin by virtue of the need for fms-related tyrosine kinase (Flt)3 expression for their development [56]. Flt3 is a cytokine receptor that is highly expressed in bone marrow lymphoid progenitors and also in rare myeloid progenitors with lymphoid potential [57]. Recent data have shown that nuocytes are derived from common lymphoid progenitors (CLPs) in the bone marrow [56,58].…”
Section: Reviewmentioning
confidence: 99%
“…To explain the complexity going forward, to develop a detailed hierarchy of stem cells, we can take a look at the HSCs after decades of research. Additional information is evolving on these stem cells, indicating that the mapping of lineages continues to be a subject in progress [15] . Thus, therapies will be developed in the realm of unresolved science.…”
Section: Cscsmentioning
confidence: 99%